THEORETICAL STUDY OF NONLINEAR OPTICAL PROPERTIES IN 3-SUBSTITUTED-4-AMINO-4'-NITRO DIPHENYLSULFIDE - Incháustegui, Jean P. (2014)
This work identifies the structural and optical properties of species 4-amino-4'- nitrodiphenilsulfide such as: static dipole moment (ì), mean polarizability (á0), anisotropy of the polarizability (Äá) and the first hyperpolarizability average (â0). Data were obtained through the theory of the density functional, using B3LYP hybrid functional and feature 6- 31G basis.